2016
DOI: 10.1136/annrheumdis-2016-209540
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre randomised controlled trial to compare the pharmacokinetics, efficacy and safety of CT-P10 and innovator rituximab in patients with rheumatoid arthritis

Abstract: ObjectiveTo demonstrate pharmacokinetic equivalence of CT-P10 and innovator rituximab (RTX) in patients with rheumatoid arthritis (RA) with inadequate responses or intolerances to antitumour necrosis factor agents.MethodsIn this randomised phase I trial, patients with active RA were randomly assigned (2:1) to receive 1000 mg CT-P10 or RTX at weeks 0 and 2 (alongside continued methotrexate therapy). Primary endpoints were area under the serum concentration–time curve from time zero to last quantifiable concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 9 publications
5
72
1
4
Order By: Relevance
“…PK results in this study were similar to those observed in a Phase 1 study comparing CT-P10 to EU-RTX. 10 Importantly, in this report the PK was also shown to be equivalent between CT-P10 and US-RTX. Considering the equivalence of EU-RTX and US-RTX shown in Part 1, it is appropriate to assess efficacy equivalence of CT-P10 against a combined RTX group, where both PK and efficacy of CT-P10 could be considered “as equivalent” to each form of RTX as each of these reference products was to each other.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…PK results in this study were similar to those observed in a Phase 1 study comparing CT-P10 to EU-RTX. 10 Importantly, in this report the PK was also shown to be equivalent between CT-P10 and US-RTX. Considering the equivalence of EU-RTX and US-RTX shown in Part 1, it is appropriate to assess efficacy equivalence of CT-P10 against a combined RTX group, where both PK and efficacy of CT-P10 could be considered “as equivalent” to each form of RTX as each of these reference products was to each other.…”
Section: Discussionsupporting
confidence: 50%
“…We are therefore satisfied that there is sufficient assurance that individual PK concentration levels seen with CT-P10 and reference products are likely due to random fluctuations, and not any intrinsic properties of either drug. 10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in patients with newly diagnosed advanced FL showed pharmacokinetic similarity between a potential biosimilar to rituximab, CT-P10, and rituximab (each administered with CVP), with similar B-cell kinetics and immunogenicity 45. In another study, CT-P10 and rituximab showed equivalent pharmacokinetics, and comparable efficacy, pharmacodynamics, immunogenicity, and safety in patients with RA 46. A clinical study in patients with previously untreated FL showed therapeutic equivalence in overall response rate between another proposed biosimilar to rituximab, GP-2013, and rituximab sourced from the EU.…”
Section: The Advent Of Rituximab Biosimilars: Where Are We Now?mentioning
confidence: 97%
“…At week 102, ACR20, ACR50, and ACR70 response rates were 71.8%, 51.4%, and 26.1% in the switch (from INX to CT-P13) group and 71.7%, 48%, and 24.3% in the maintenance group, respectively. The response rates were maintained from weeks 54 to 102 in both groups 33. In this case, the proportion of patients reporting at least one TEAE was more balanced between the maintenance and the switch group (63.5% vs 62.2%), as well as the rate of TEAEs classified as related to treatment (22% vs 18.9%), and the incidence of infusion-related reaction (6.9% vs 2.8%), latent tuberculosis (5.7% vs 2.8%), upper respiratory tract infection (3.8% vs 2.1%), lower respiratory tract infection (2.5% vs 2.8%), abnormal liver function test (0.6% vs 2.8%), and urinary tract infection (1.3% vs 1.4%) 33…”
Section: Introductionmentioning
confidence: 99%